Polypharmacological assessment of amoxicillin and its analogues against the bacterial DNA gyrase B using molecular docking, DFT and molecular dynamics simulation - Miah, Roney; Singh, Gagandeep; Dubey, Amit; Soni, Hemant; Tandon, Smriti; Narasimhaji, Cheemlapati Venkata; Tufail, Aisha; Akm, Moyeenul Huq; Mohd Fadhlizil Fasihi, Mohd Aluwi (Elsevier B.V., 2023)
There has been an increase in the emergence and spread of drug-resistant pathogens, leading to a steep incline in the cases of antimicrobial resistance. Due to this, there is an imperative need for the development and identification of new antimicrobials to combat this menace of antimicrobial resistance. But this need is not being completely fulfilled by conventional drug discovery focused on a one molecule-one target approach. Polypharmacology, i.e., designing a drug in a way that acts on multiple cellular or molecular targets, a new approach for the identification of antimicrobial compounds, has been gaining attention. DNA gyrase B is one of the critical proteins involved in DNA replication and cell division in E. coli. In this study, the polypharmacological effect of amoxicillin and its analogues was studied on the DNA gyrase B and various other proteins of E. coli, using multiple in silico approaches like molecular docking, structural similarity, DFT, and molecular dynamics simulation. Both amoxicillin and its analogue, Cefaclor, tend to disrupt bacterial cell wall synthesis, but this study, based on in silico analysis, suggests a probable additional mode of action involving DNA gyrase B of E. coli which can be further explored to design novel dual-target inhibitors.